Partisipasi Tenaga Kerja Pemuda di Sektor Pertanian di Sulawesi Tengah - Nurdiyanto, Eka; Sukamdi, nFN; Rofi, Abdur (Analisis Kebijakan Pertanian, 2020)
Structural transformation in Central Sulawesi has led to a decline in the contribution of agricultural sector in the province’s economy. In addition, the phenomenon of increasing aging farmers was one of the problems in improving the agricultural sector performance. This study aimed to examine factors that influence youth labor participation in the agricultural sector in Central Sulawesi. The data used in this research was Sakernas 2018 published by Statistics Indonesia (BPS). The analysis was carried out in three levels, namely individual, household, and contextual levels, using a multilevel binary logistic analysis. Results of this analysis showed that youth labor participation in the agricultural sector was significantly influenced by the several factors: for individual factors were level of education and gender; household socioeconomic factors were education level of household heads, occupations of household heads, and number of household members; and the region contextual factors were population density and Gross Regional Domestic Products (GRDP) per capita. To increase youth labor participation in this province, it is recommended that the local government to implement programs to change youth perceptions of work opportunity in the agricultural sector, create agricultural diversification, improve welfare of agricultural households, strengthen agricultural market strategies. and enhance the skills and capacity of agricultural youth.